Queer generations: Theorizing a concept. (July 2019) - Marshall, Daniel; Aggleton, Peter; Cover, Rob; Rasmussen, Mary Lou; Hegarty, Benjamin
This article reflects on the concept of 'queer generations' as developed in the context of an ongoing study about belonging and sexual citizenship among two social generations of gender and sexual minority youth in Australia. We define the concepts 'queer' and 'generations' in the context of recent theoretical interest in temporality in childhood and youth studies in an attempt to think differently about gender and sexual difference. The main theoretical tension that lies at the heart of this article is how to take seriously the shared experience of growing up LGBT without insisting on a uniform narrative that is inherent to it. Drawing on an archival fragment from an HIV campaign produced in Australia and distributed in the 1990s and targeted at young gay and bisexual men, we consider the shifting conditions through which visibility has featured as a key problem for the deployment of sexual citizenship. This archival fragment is valuable because of the way that it problematizes the in/out, visible/invisible, gay/straight binaries that have dogged attempts to grapple with the at once individual and collective experience of growing up LGBT. The concept of 'queer generations' suggests critical insights into the limits and affordances of the production of generations as containers for generalized experience.